ANALYSIS OF USER SATISFACTION OF ONLINE MOTORCYCLE TAXI APPLICATIONS USING THE LITERATURE REVIEW METHOD - Nay Marbintang, Fadillah; Andania, Rafika; Indriyana, Balqis; Wandari, Rizky; Salsabila, Lisa; Samroiyah, Juwita (Pena Cendekia Insani, 2023)
Technological developments have brought major transformations in the transportation sector, one of which is through the presence of online motorcycle taxi applications such as Gojek and Grab. This study aims to analyze user satisfaction of online motorcycle taxi applications using the literature review method. Data is collected from relevant scientific journals, articles, and research reports. The main factors that affect user satisfaction include service quality, price, ease of use of the application, and features offered. The results of this study provide insights for application developers to improve service quality and meet user expectations.